Analisis Marketing Mix Terhadap Target Penjualan Kafe DR. Koffie - Pratama, Agung Jhoniko; Rachman, Muhamad Emil (Jurnal EMT KITA, 2023)
Nowadays, consumers visit cafes or coffee shops not only for consumption purposes, but also as a place to spend free time, hold work meetings and meet with relatives. This phenomenon has created intense competition and given rise to various problems, one of which is related to the Kafe DR. Koffie Cafe. Problems faced by DR. Koffie Cafe includes unstable sales fluctuations and a decrease in buying interest from the public. In this research, the analysis method used is SWOT (Strengths, Weaknesses, Opportunities, Threats) with DR. Koffie Cafe consumers. The results of the SWOT analysis show that DR. Koffie Cafe is in quadrant I, which is a very favorable situation. In this quadrant, DR. Koffie Cafe has opportunities and strengths that can be exploited. Therefore, DR. Koffie Cafe needs to implement a strategy that supports aggressive growth (Growth-oriented strategy) to achieve the sales targets that have been set.